2018
DOI: 10.3329/dujps.v17i1.37129
|View full text |Cite
|
Sign up to set email alerts
|

Study of Bioactivities of Holarrhena pubescence Growing in Bangladesh

Abstract: ABSTRACT:The stem bark of Holarrhena pubescence was tested for anti-diabetic, analgesic, anti-inflammatory and antidiarrheal activities. After 1, 4 and 12 weeks of treatment protocol in alloxan-induced diabetic rats, it showed very negligible reduction of blood glucose level. In 12 weeks treatment protocol H. pubescence demonstrated that, the extract at 300 and 600 mg/kg bw can reduce blood glucose level by 3 and 4 mmol/l, respectively. Bark extract possessed strong analgesic, anti-diarrheal and mild anti-infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Effective storage capacity has been calculated to estimate total volume of CO 2 that can be injected. The reservoir temperature and thermal gradient data (Table 4 ) are collected from 87 . The structural area (Table 4 ) calculated from the top to spill point on a seismic section.…”
Section: Resultsmentioning
confidence: 99%
“…Effective storage capacity has been calculated to estimate total volume of CO 2 that can be injected. The reservoir temperature and thermal gradient data (Table 4 ) are collected from 87 . The structural area (Table 4 ) calculated from the top to spill point on a seismic section.…”
Section: Resultsmentioning
confidence: 99%
“… They are utilised as an astringent, anthelmintic, febrifuge, stomachic, anti-dysenteric, and anti-diarrheal in the native medical system of Bangladesh [60] .  They are apparently used in other regions of the world to treat diuresis, chronic chest infections, asthma, malaria, vaginitis, diabetes, arthritis, hematuria, epilepsy, bronchitis, diarrhoea, dermatitis, and jaundice [61] , according to reports (Figure 1). [80] Table 11: Pharmacological activities of Holarrhena pubescens No.…”
Section: Seedsmentioning
confidence: 99%
“…The Singra well, with over 150 °C bottom hole temperature holds the most auspicious position among the three areas [ 9 ]. Barapukuria coal basin and the Madhyapara hard rock mine area are two other potential zones for geothermal energy, among which the latter was found with a temperature variation in the range of 67°–153 °C, indicating the presence of a low-temperature geothermal reservoir in the area [ 16 ]. Moreover, it is found that the temperature at 2500 m below the earth's surface in the northwestern tip of Bangladesh, near Salbanhat-1 well, was 79 °C and at a depth of 4,000 m it increased to 110 °C [ 17 ].…”
Section: Geothermal Energy Potentialmentioning
confidence: 99%
“…However, the subsurface temperature distribution at different depths leads to the feasibility analysis for energy extraction from geothermal resources [ 16 ]. Figure 5 illustrates the subsurface temperature distribution of different areas in southeast regions [ 20 , 21 ].…”
Section: Geothermal Energy Potentialmentioning
confidence: 99%